Microbially Induced Sedimentary Structures (MISS) and their Involvement in Sediment Stabilization and Formation of Gravelly Coastal Landforms (Berms, Spits and Bars) in Salman Hypersaline Lagoon, Red Sea Coast of Saudi Arabia - Mannaa, Ammar (Journal of King Abdulaziz University: Marine Sciences, 2021)
This study documents the occurrence of several MISS such as laminated microbial mats, biostabilized ripples, gas domes, mat folds, erosional pockets and remnants, microbial cracks, and gypsified mat chips in Salman hypersaline lagoon, north Jeddah city, Saudi Arabia. This study indicates that both microbial and physical processes are reponsible for sediments biostablization and formation of spits, bars and berms. It focuses on the role of waves generated by winds in erosion of the microbially, biostabilized sediments and their deposition on the eastern shore of the semi-closed Salman lagoon. In winter months, the floor of the lagoon shows a rippled surface that mantled with green to black microbial mats. In summer months, gypsum crystals grow on the surface of the mats and develop a gypsified microbial crust. A slight agitation of the lagoonal water in winter months partially erodes the mat layer and impart a black stain to the water column of the lagoon. In summer months, strong agitation of the waves generated by winds in the lagoon leads to erosion of the gypsified micribial crusts and underlying bioclastic and gypsum layers into gravelly mat chips that leave erosion pockets surrounded with erosion remnants. The gravely, eroded sediments are transported by a longshore current and deposited on the eastern shore of the lagoon as berms, spits and bars. The spits and bars enclose small, shallow pools filled with mud sediments. The result of this study provides useful data to elucidate processes of change in coastal landforms due to bio-stabilization by microbial mats and their erosion by waves induced by wind.